3D Printed Gallium Battery with Outstanding Energy Storage: Toward Fully Printed Battery-on-the-Board Soft Electronics - Calisto Freitas, Marta (2024)
The last decade observed rapid progress in soft electronics. Yet, the ultimate desired goal for many research fields is to fabricate fully integrated soft-matter electronics with sensors, interconnects, and batteries, at the ease of pushing a print button. In this work, an important step is taken toward this by demonstrating an ultra-stretchable thin-film Silver-Gallium (Ag-Ga) battery with an unprecedented combination of areal capacity and mechanical strain tolerance. The Biphasic Gallium-Carbon anode electrode demonstrates a record-breaking areal capacity of 78.7 mAh cm−2, and an exceptional stretchability of 170%, showing clear progress over state-of-the-art. The exceptional theoretical capacity of gallium, along with its natural liquid phase self-healing, and its dendrite-free operation permits excellent electromechanical cycling. All composites of the battery including liquid-metal-based current collectors, and electrodes are sinter-free and digitally printable at room temperature, enabling the use of a wide range of substrates, including heat-sensitive polymer films. Consequently, it is demonstrated for the first time multi-layer, and multi-material digital printing of complex battery-on-the-board stretchable devices that integrate printed sensor, multiple cells of printed battery, highly conductive interconnects, and silicone chips, and demonstrate a tailor-made patch for body-worn electrophysiological monitoring.